The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/eb-2017-102664
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety apps: a systematic review and assessment of app descriptors across mobile store platforms

Abstract: Question The aim of this systematic review is twofold: (1) to characterise the purpose and description of available social anxiety apps and (2) to review the evidence on the effectiveness of social anxiety apps. Study selection and analysis A search was conducted on three major mobile platforms: Apple iTunes, Google Play and Windows Store. Apps were included if they addressed social anxiety and used an English language interface. A systematic review of the literature from MEDLINE, EMBASE, PsycINFO, Cochrane, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 45 publications
4
50
0
4
Order By: Relevance
“…We found that participant concerns around this issue could be allayed if a trusted source endorsed the system. However, recent reviews of publically available smartphone apps revealed that less than a quarter of those available for bipolar disorder included a privacy policy [ 39 ] and less than 10% of those available for social anxiety provided organization information [ 40 ]. This contrast between current information provided on publically available mental health smartphone apps and the preference of service users for DHIs from trusted sources suggests that content information currently available may not be sufficient to alleviate service user privacy concerns, thus potentially negatively impacting engagement.…”
Section: Discussionmentioning
confidence: 99%
“…We found that participant concerns around this issue could be allayed if a trusted source endorsed the system. However, recent reviews of publically available smartphone apps revealed that less than a quarter of those available for bipolar disorder included a privacy policy [ 39 ] and less than 10% of those available for social anxiety provided organization information [ 40 ]. This contrast between current information provided on publically available mental health smartphone apps and the preference of service users for DHIs from trusted sources suggests that content information currently available may not be sufficient to alleviate service user privacy concerns, thus potentially negatively impacting engagement.…”
Section: Discussionmentioning
confidence: 99%
“…There are several evidence-based frameworks that inform PTSD psychological treatments (as mentioned above), and it would seem plausible that such treatment interventions could be incorporated into an app. There needs to be expert input from qualified clinicians and/or researchers into the development of a mental health app-many apps claiming to treat symptoms of mental illness do not have such input (25,43,44). Given that the development of mobile mental health apps is still in its infancy, we are still not certain about the mechanisms of action of such apps, and therefore the level of importance of characteristics such as app design and usability is still being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We first developed a review protocol based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement recommendations 13. Our methodology with regards to identification and categorisation was in accordance with previous systematic app reviews 14. Building on our findings, we performed a structured qualitative content analysis15 of the included app descriptions.…”
Section: Methodsmentioning
confidence: 99%